Validation of the Cell Phone Dependence Scale - King,Anna Lucia Spear (2019)
BACKGROUND INFORMATION: The boundary between cellphone use and abuse is quite tenuous. Research is required to evaluate the use of this device interacting in the everyday life of users, whether to speak or to perform tasks. OBJECTIVE: To construct a novel and specific scale to evaluate cellphone dependence checking its psychometric properties for clarity, accuracy and reliability. METHODS: Validation of a Cellphone Dependence Scale (CPDS) was performed in 5 phases: 1- initial scale construction with 20 questions, 2- expert evaluation, 3- application to 200 volunteers, 4- statistical analysis and results, and 5- elaboration of the final version of the CPDS. RESULTS: We used the R statistical program Version 3.4.2 and the “dplyr” package to present the descriptive statistics, the hypotheses tests of differences of means and the factorial analysis. The results provided a validated and accepted final version for CPDS. The last step of the study was to calculate Cronbach’s alpha, in order to measure the internal consistency of the questionnaire. The value found was 0.897, which is considered very good. CONCLUSIONS: This project resulted in the construction of the final CPDS version suitable for the clinical context and to be used in the conduct of research on cellphone dependence. CPDS may contribute to future studies, conscious use of cellphones, harm reduction, and improved quality of life vis-à-vis the cellphone.